Effect of Ajwa Date and Germinated Barley on Lipid Profile in Rats Fed High-Fat Diet - Rana Alduwayghiri; Reham M. Algheshairy (Applied Sciences, 2023)
High levels of lipids and cholesterol, particularly LDL, in blood are considered the most common risk factors for cardiovascular diseases that threaten human life. Recently, interest has increased in the use of medicinal plants to treat various diseases due to their lack of side effects. The current study aims to investigate the effect of Ajwa date (AD) and germinated barley (GB) on the lipid profile in rats fed a high-fat diet (HFD). Thirty rats were distributed into five groups (six per group) as follows: the negative control group, the positive control group fed a HFD, and the other three groups that were fed a HFD supplemented with a mixture of AD and GB in equal ratios with different proportions of 20, 30, and 40% in the diet. There was an increase in moisture, protein, phenols, and vitamin C content and a decrease in the content of ash, carbohydrates, fats, and beta-glucans in GB. Blood total cholesterol levels decreased significantly (83.53, 70.12, and 73.55 mg/dL) in the groups fed the AD and GB mixtures in different percentages (20, 30, and 40%). Likewise, the AD and GB mixtures recorded a significant decrease in the level of triglycerides in the treated groups, with no significant effect on the high-density lipoprotein and low-density lipoprotein. There was a significant improvement in the level of alanine aminotransferase, while the level of aspartate aminotransferase was not affected by the treatment. In summary, AD and GB mixtures can modulate the lipid profile alterations caused by HFD through their phytochemical constituents, particularly beta-glucans.